Avaliação da oscilação corporal de indivíduos com e sem dor lombar após caminhada de 10 minutos - Morais, Sandra Cristina da Veiga (2016)
Subjects with low back pain (DL) have adaptations while walking as a result of pain, and these adjustments are likely to affect the postural control of these subjects. However, among the recommended aerobic physical activity, walking is known as a safe exercise with low injury rate. Thus, it is necessary to analyze the behavior of body sway of subjects with DL through force platform before and after a 10 minute walk on the treadmill, in order to observe whether it is activity generates some influence on the balance of individuals. Materials and Methods: The sample consisted of 35 subjects, divided into two groups: Group DL (n = 20) and group without DL (n = 15). The body sway was collected on a force platform AMTI model OR6-6-200 before and after hiking for this activity was used a treadmill of Polimet brand, EP-1600 model. Individuals with DL passed through a physiotherapeutic APPRAISAL from tests indicated by Sullivan that are capable of classifying the origin of the DL. In the data analysis was performed using the Statistical Package for the Social Scienses (SPSS) version 15.0. The data collected before and after the walk passed the Shapiro Wilks normality test, when the data were normal was applied the paired t-test and when the data were not normal, applied the nonparametric Wilcoxon test. Results: The data showed that the DL group had strategies in relation to the balance control similar to the group without DL. Conclusion: static balance did not change in the population studied after the assessed activity. Thus, considering the body sway, a 10-minute walk of activity can be prescribed without modification on it.